Association Between Polypharmacy and Cardiovascular Outcomes in Frail Elderly Patients: Systematic Review and Meta-Analysis - Virk, Ghazala S.; Munir, Ahsan; Alim, Wala; Zia, Usman; Ali, Layla Hago Mustafa; Mohammed, Samah; Deepak, FNU; Ogeil, Mahdi; Indiresh, Dhruv; Abid, Marium; et al. (Cardiology and Cardiovascular Medicine, 2025)
Polypharmacy, which is the simultaneous use of five or more pharmacological agents, is still prevalent in old people, particularly frail ones with numerous comorbidities. This current systematic review and metaanalysis aimed to explain the effects of polypharmacy on the cardiovascular outcomes of this vulnerable group. The search was conducted in PubMed, Scopus, Cochrane Library, and Google Scholar, including all studies that were published between 2020-2025. The focus of the inquiry was on the consequences of polypharmacy to cardiovascular health, major adverse cardiovascular events (MACE), cardiovascular mortality, heart failure hospitalizations, and functional deterioration. Randomized controlled trials (RCTs) and cohort studies were both included. The meta-analysis involved the use of a random-effects model to determine the pooled effect size. The above synthesis showed a significant relationship between polypharmacy and adverse cardiovascular outcomes, and the effect size was 0.93 (95% CI: 0.48-139). These results suggest that polypharmacy significantly increases the chances of developing cardiovascular complications in frail elderly patients. There was a very large heterogeneity, and I2 was 96.30%. It is believed that the possible causes of this heterogeneity comprise variations in study design, characteristics of participants, and outcomes. Risk-of-bias evaluation highlighted significant disparity among studies, with certain studies characterized as having low risk of bias and others rated as having moderate-to-high risk. There was no publication bias, as testified by the symmetrical funnel plot, and no statistical significance of the Egger test. Nevertheless, in spite of these weaknesses, the results of the research point to the high adverse outcome of polypharmacy on cardiovascular measures in frail elderly adults. Thus, it underlines the necessity of medication review and deprescribing interventions in this patient group.